International sport marketing: practical and future implication - Zemikael Getu (Publikasi Indonesia, 2023)
The principles and tools of sport marketing represent the essential knowledge sport managers require in order to position their sport, association, club, team, player, code or event in the highly competitive sport market. This article explains the principles and tools of marketing sport organisations, marketing mix, tourist orientation, segemetation strategy, communication mix and framework for targeted sport event packaging. The purpose of this article is to introduce the core philosophy and process of sport marketing. It will introduce some basic marketing concepts, and will outline the Sport Marketing Framework.